Potential of a Lesser Known Tree Species Parkia roxburghii G. Don of North East India - Rathi, R. S.; Misra, A. K.; Roy, Somnath; Verma, S. K.; Singh, S. K. (Indian Forester, 2012)
Parkia roxburghii G. Don is a lesser known multipurpose tree species of family Mimosaceae. It grows abundantly in the North Eastern region of India, especially in Manipur, Mizoram and Nagaland. It has significant economic values as vegetable, medicinal, Industrial and fire wood in this region. It is a fast growing, easier to grow and hardy in nature. It produces a crop even under adverse soil and climatic conditions. This tree is suitable for reclamation of abandoned Jhum lands and also as agro-forestry plantations. If properly exploited, it can serve as supplementary source of vegetable proteins and edible oil.